Overexpression of Specific Cysteine Peptidases Confers Pathogenicity to a Nonpathogenic Entamoeba histolytica Clone - Jenny Matthiesen (American Society for Microbiology, 2013)
ABSTRACT Cysteine peptidases (CPs) of Entamoeba histolytica are considered to be important pathogenicity factors. Previous studies have found that under standard axenic culture conditions, only four (ehcp-a1, ehcp-a2, ehcp-a5, and ehcp-a7) out of 35 papain-like ehcp genes present in the E. histolytica genome are expressed at high levels. Little is known about the expression of CPs in E. histolytica during amoebic liver abscess (ALA) formation. In the current study, a quantitative real-time PCR assay was developed to determine the expression of the various ehcp genes during ALA formation in animal models. Increased expression of four ehcp genes (ehcp-a3, -a4, -a10, and -c13) was detected in the gerbil and mouse models. Increased expression of another three ehcp genes (ehcp-a5, -a6, and -a7) was detected in the mouse model only, and two other ehcp genes (ehcp-b8 and -b9) showed increased expression in the gerbil model only. Trophozoites of the nonpathogenic E. histolytica HM-1:IMSS clone A1, which was unable to induce ALAs, were transfected with vectors enabling overexpression of those CPs that are expressed at high levels under culture conditions or during ALA formation. Interestingly, overexpression of ehcp-b8, -b9, and -c13 restored the pathogenic phenotype of the nonpathogenic clone A1 whereas overexpression of various other peptidase genes had no effect on the pathogenicity of this clone. IMPORTANCE Entamoeba histolytica is a widespread and clinically important protozoan parasite. It normally exists in the human intestine without causing clinical symptoms but can invade the intestinal mucosa, which causes serious intestinal (amoebic colitis) and extraintestinal (amoebic liver abscess [ALA]) diseases. The identification of factors responsible for the invasion of the parasite and disease formation is a major topic in the field. Here, we investigate the roles of different papain-like cysteine peptidases (CPs) as pathogenicity factors. We show that the expression of some of the peptidases that are normally expressed at low levels increases during ALA formation. Furthermore, nonpathogenic amoebae can be transformed to pathogenic amoebae, simply by specific overexpression of some of these CPs. Our findings reinforce the importance of CPs as pathogenicity factors of E. histolytica.